Treatment Outcome and Factors Affecting Mortality among Patients with Liver Injuries in Mae Sot General Hospital, Tak Province, 2003-2007 - Jittakarn, Somchet (Journal of Health Science of Thailand, 2018)
The liver is frequently injured in both blunt and penetrating trauma. This report presented characteristics, causes and mechanism of injuries, clinical features, severity, associated injuries, treatment outcome, and factors potentially affecting mortality among patients with liver injuries in Mae Sot General hospital, Tak Province. Medical records of 48 patients with liver injuries in the hospital during 2003-2007 were reviewed. Of the cases, 89.6 percent were male and 41.7 percent were 25-34 years old. The mean age of the cases was 28 years old. About 52.1 percent were Myanmar migrants. The main causes of injuries were violence (58.3%) and road traffic injuries (37.5%). The median of duration between injury occurrence and hospital arrival was 2 hours. About 58.3 percent had penetrating injuries and 41.7 percent had blunt trauma. Of the cases, 60.4 percent experienced peritonitis and 12.5 percent had hemorrhagic shock. The severity of liver injuries most frequently detected in the cases was grade II (41.7%), followed by grade IV (16.7%). The median of duration between arrival at the emergency room and the operating room was 1 hour. About 81.3 % had associated injuries, mostly the diaphragm for the organ in the abdominal cavity and the lung for the organ outside the abdomen. Half of the cases had liver suture and 39.6 percent had perihepatic packing. The estimated blood loss £ 1,000 ml was found in 47.9 percent of the cases and from 1,001-2,000 ml in 18.8 percent. The most commonly reported complications were hemorrhagic shock (12.5%) and pneumonia (4.2%). The median length of hospital stay was 7 days. The median cost of treatment was 25,635 baht. The mortality rate of the cases was 29.2 percent. Factors significantly affecting mortality were the severity of liver injuries and the volume of blood loss. Operative treatment remains essential for the liver injury. Prevention measures to reduce the occurrence of injuries may be useful. Key words: liver injury, blunt injury, penetrating injury, mortality